2012
DOI: 10.3109/10428194.2012.751528
|View full text |Cite
|
Sign up to set email alerts
|

Early versus delayed autologous stem cell transplant in patients receiving novel therapies for multiple myeloma

Abstract: Autologous stem cell transplant (ASCT) is an effective treatment for multiple myeloma (MM). However the timing of ASCT in the era of novel agents (lenalidomide, thalidomide, bortezomib) is unknown. We retrospectively reviewed the outcome of MM patients who received novel agent based induction treatment and received first ASCT within 12 months of diagnosis (early ASCT, N = 102), or at a later date (late ASCT, N = 65). Median time to ASCT was 7.9 months vs. 17.7 months in the early vs. late ASCT. The 3 and 5 yr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 26 publications
1
29
0
1
Order By: Relevance
“…17,29,30 Given the striking efficacy of RVD [with overall response rates of 100% and near complete or complete remission (CR) rates of 52% seen in phase 2 populations] and the remarkable results of CRD, with 63% near CR or better reported, randomized studies incorporating both proteasome inhibition and prolonged maintenance are obviously key. 18,31…”
Section: Best Induction Regimens In the Novel Agent Era With The Intementioning
confidence: 99%
“…17,29,30 Given the striking efficacy of RVD [with overall response rates of 100% and near complete or complete remission (CR) rates of 52% seen in phase 2 populations] and the remarkable results of CRD, with 63% near CR or better reported, randomized studies incorporating both proteasome inhibition and prolonged maintenance are obviously key. 18,31…”
Section: Best Induction Regimens In the Novel Agent Era With The Intementioning
confidence: 99%
“…One study reported the outcomes of 290 patients treated with IMiDs based therapy (thalidomide or lenalidomide) and that received early (within 12 mo of diagnosis) or late ASCT; PFS was similar irrespective of when ASCT was performed (early or late) and no significant difference could be observed in OS, with both groups experiencing a 4-year OS of 73% [48] . In a similar study Dunavin et al [47] retrospectively reviewed the outcome of 167 patients treated with novel agent-based therapy (IMiDs or PI) and receiving early or delayed ASCT. The 5-year OS from diagnosis was similar in the two groups (63% both in early and late ASCT, P = 0.45), in accordance with the data reported by Kumar et al [48] .…”
Section: Orr (%) Pfs (Mo) Os (Mo)mentioning
confidence: 99%
“…Cook et al [49] 2011 106 Retrospective 19 mo (relapse from first transplant) Yes 63% NR 37 Jimenez-Zepeda et al [51] [45] 2013 187 Retrospective 32 mo Yes 68% 5% at 5 yr 29% at 5 yr Shah et al [68] Brioli A. ASCT in MM in some cases given as a salvage treatment after a previous ASCT [44][45][46] , whilst in others patients received ASCT after relapsing from a treatment not including transplantation [29,47,48] . One of the biggest records is the one published by Sellner et al [44] , in which 200 MM patients retreated with ASCT at the time of relapse were retrospectively analysed.…”
Section: Orr (%) Pfs (Mo) Os (Mo)mentioning
confidence: 99%
See 2 more Smart Citations